The Third Theorem of Welfare Economics: Report from a Fictional Field Study - Karine Nyborg (Institute of Labor Economics (IZA), 2019)
The perfectly competitive market – a hypothetical situation free of market failure – is the basis for the two fundamental welfare theorems, and an important benchmark for economic theory. The radical abstractions of this idea, however, make its full implications hard to grasp. I address this using literary fiction. Part I discusses fiction as a tool for economic theory. Part II is a story about a journey to the perfectly competitive market. Part III develops main theoretical insights based on the story: First, complete social isolation is needed to preclude market failure. Second, the requirements of symmetric information and no external effects are extremely hard to reconcile, leading to an impossibility theorem: if trade is permitted anytime, and deliberate, welfare-relevant learning is feasible, no perfectly competitive market can exist.
Keywords: A11; D60; D62; D82; 330; perfect competition; narratives; social interaction; symmetric information; complete contracts; labor markets